Quilting Resistance to the Sleep Industrial Complex: A Narrative Account of Sleeplessness - Serota, Kristie (Art/Research International, 2021)
In this narrative account of sleeplessness, I draw on Ball’s (2002, 2012) poststructural conceptualization of quilts as social texts to explore the practice of quilting as a method of arts-based storytelling. Through the process of quilting, I story my experience of resisting the Sleep Industrial Complex. I explore the biocultural arena of sleep and critique the biomedical construction of sleeplessness as insomnia. I argue that the medicalization of sleeplessness works to support multi-billion-dollar industries that purport to cure insomnia through consumerism (Barbee et al., 2018; Williams, 2008). I describe how radically accepting sleeplessness as a facet of my existence, and not a medicalized disorder, is an expression of self-acceptance and an act of self-care. In this arts-based narrative account of sleeplessness, I mark the transition from viewing sleeplessness as a medical disorder to radically accepting sleeplessness as a natural facet of our complex being-in-the-world.